Rapid formation of plasma protein corona critically affects nanoparticle pathophysiology - Tenzer, Stefan; Docter, Dominic; Kuharev, Joerg; Musyanovych, Anna; Fetz, Verena; Hecht, Rouven; Schlenk, Florian; Fischer, Dagmar; Kiouptsi, Klytaimnistra; Reinhardt, Christoph; Landfester, Katharina; Schild, Hansjoerg; et al. (Nature nanotechnology, 2013)
In biological fluids, proteins bind to the surface of nanoparticles to form a coating known as the protein corona, which can critically affect the interaction of the nanoparticles with living systems. As physiological systems are highly dynamic, it is important to obtain a time-resolved knowledge of protein-corona formation, development and biological relevancy. Here we show that label-free snapshot proteomics can be used to obtain quantitative time-resolved profiles of human plasma coronas formed on silica and polystyrene nanoparticles of various size and surface functionalization. Complex time- and nanoparticle-specific coronas, which comprise almost 300 different proteins, were found to form rapidly (<0.5 minutes) and, over time, to change significantly in terms of the amount of bound protein, but not in composition. Rapid corona formation is found to affect haemolysis, thrombocyte activation, nanoparticle uptake and endothelial cell death at an early exposure time. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-10-13